The Intricacies of Academic Remuneration - Altbach, Philip (International Higher Education, 2009)
Salaries among academics may vary drastically, based on tenure, type of institution, country, research activity and other factors. The ability of faculty members to subsist on their compensation varies across the globe, and may influence research and publication output, and migration of faculty to higher paying countries, institutions or fields.